STRATEGI PENGEMBANGAN PENYULUHAN PROGRAM PEKARANGAN PANGAN LESTARI SELAMA MASA PANDEMI COVID-19 - Aifah Ari Mandini; M. H. Jamil; N. M. Viantika; N. Lanuhu; Rahmadhanih Rahmadhanih (JSEP (Journal of Social and Agricultural Economics), 2022)
Agricultural development is a process of social dynamics. One of the agricultural developments in the agricultural extension, especially in the Pekarangan Pangan Lestari (P2L) extension program which can be an answer to the current situation, namely Covid-19. This study aims to analyze the implementation of counseling, identify supporting and inhibiting factors and formulate strategies for developing P2L program extensions during the Covid-19 pandemic in Parepare City. This research was conducted from May to June 2021. The analytical method used was descriptive and SWOT analysis based on the implementation of the extension, the supporting and inhibiting factors of the P2L program extension, and the development strategy. The results showed that the implementation of the P2L program extension continued as usual but experienced changes in behavior, systems, mechanisms, and frequency of visits. In the extension development strategy during the Covid-19 where extension workers are more adaptive and innovative in every interesting extension activity. One of them is a learning process that relies on communication facilities in watching videos and materials that can be accessed on the internet flexibly which makes extension workers and group members develop their knowledge and continue to apply health protocols, especially women farmer groups who are constrained by not having digital communication facilities.